Scheme of Attribute-Based Disclosure Mobile Trust Negotiation - Qiuyun Wang; Wenbao Jiang; Hong Wang (Dianxin kexue)
For it is difficult to use traditional trust negotiation on the mobile environment,which has large communication overhead,storage overhead and computational overhead,an attribute-based disclosure mobile trust negotiation scheme was proposed.In the negotiation process,two sides in trust negotiation exchange certificate which contains encrypted credential attributes firstly,then,one side in trust negotiation can selectively dispose the sensitive attributes to the other side in trust negotiation procedure based on the trust evaluation result of the other,next,two sides in trust negotiation exchange attribute encryption key based on personal security policy until the trust negotiation was completed.The implementation procedure was given in concrete application instances and the scheme was analyzed.